2020
DOI: 10.1177/0310057x20958716
|View full text |Cite
|
Sign up to set email alerts
|

The gap between attitudes and processes related to ‘family-friendly’ practices in anaesthesia training in New Zealand: A survey of anaesthesia supervisors of training and departmental directors

Abstract: Gender inequity persists within the anaesthetic workforce, despite approaching numerical parity in Australia and New Zealand. There is evidence, from anaesthesia and the wider health workforce, that domestic gender norms regarding parental responsibilities contribute to this. The creation of ‘family-friendly’ workplaces may be useful in driving change, a concept reflected in the gender equity action plan developed by the Australian and New Zealand College of Anaesthetists. This study aimed to explore the exten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Second, there may be some barriers ("glass ceiling") against reaching leadership positions [31,32]. Numerous reports have indicated that women are more likely to face difficulties when climbing the career ladder [33][34][35][36][37]. Additionally, women are relatively less willing to become leaders [38].…”
Section: Discussionmentioning
confidence: 99%
“…Second, there may be some barriers ("glass ceiling") against reaching leadership positions [31,32]. Numerous reports have indicated that women are more likely to face difficulties when climbing the career ladder [33][34][35][36][37]. Additionally, women are relatively less willing to become leaders [38].…”
Section: Discussionmentioning
confidence: 99%
“…In New Zealand, many anesthesia training hospitals lack sufficient lactation spaces. 14 At a university (not in Iowa), half of 223 surveyed female physicians reported "lack of appropriate place to pump breastmilk" as a barrier to breastfeeding. 2 At a third university, qualitative study of female physicians found that proximity of lactation space to operating rooms was a barrier to breastfeeding.…”
Section: Discussionmentioning
confidence: 99%
“…Choosing a career in medicine also influences the child-rearing decisions of female physicians 6 . Potential barriers to career progression at the child-rearing age include gender discrimination after giving birth, prejudicial treatment because of breastfeeding, lack of extended maternity and paternity leave and stigmatisation of part-time training 7–10 . In a US study on parenthood-related factors, 1 in 10 women anaesthesiologists were found to counsel female trainees against furthering their careers in anaesthesiology because of obstacles related to child-rearing 8 .…”
Section: Introductionmentioning
confidence: 99%
“…6 Potential barriers to career progression at the child-rearing age include gender discrimination after giving birth, prejudicial treatment because of breastfeeding, lack of extended maternity and paternity leave and stigmatisation of part-time training. [7][8][9][10] In a US study on parenthood-related factors, 1 in 10 women anaesthesiologists were found to counsel female trainees against furthering their careers in anaesthesiology because of obstacles related to child-rearing. 8 Two recent surveys point to the same trend in Europe, with female anaesthesiologists being less likely to have children than their male counterparts.…”
Section: Introductionmentioning
confidence: 99%